Analisis Konsep Harta dalam Akuntansi Syariah terhadap Transparansi Keuangan pada UMKM Masa Kini - Eny Nasriani Arham; A. Nurul Qalbi; Filna Firani; Masyhuri Masyhuri (INDO PUBLISHING, 2026)
This study examines the concept of wealth (al-māl) in Islamic accounting and its relation to financial transparency in Micro, Small, and Medium Enterprises (MSMEs). The main problem addressed is the low level of financial transparency caused by limited accounting literacy and unstructured recording practices. A qualitative approach with a literature review method is applied by analyzing relevant academic sources on Islamic accounting and MSME financial management. The results show that wealth in Islamic accounting is not only viewed as an economic asset but also as an amanah carrying moral and spiritual responsibility. This perspective encourages more honest, transparent, and accountable financial practices. Moreover, proper application of the wealth concept improves the quality of MSME financial reporting and supports better decision-making. Thus, Islamic accounting contributes to building an ethical and transparent MSME financial system.